Spot the difference-development of a syndrome based protein microarray for specific serological detection of multiple flavivirus infections in travelers. - Natalie B Cleton; Gert-Jan Godeke; Johan Reimerink; Mathias F Beersma; H Rogier van Doorn; Leticia Franco; Marco Goeijenbier; Miguel A Jimenez-Clavero; Barbara W Johnson; Matthias Niedrig; Anna Papa; Vittorio Sambri; et al. (Public Library of Science (PLoS), 2015)
BACKGROUND:The family Flaviviridae, genus Flavivirus, holds many of the world's most prevalent arboviral diseases that are also considered the most important travel related arboviral infections. In most cases, flavivirus diagnosis in travelers is primarily based on serology as viremia is often low and typically has already been reduced to undetectable levels when symptoms set in and patients seek medical attention. Serological differentiation between flaviviruses and the false-positive results caused by vaccination and cross-reactivity among the different species, are problematic for surveillance and diagnostics of flaviviruses. Their partially overlapping geographic distribution and symptoms, combined with increase in travel, and preexisting antibodies due to flavivirus vaccinations, expand the need for rapid and reliable multiplex diagnostic tests to supplement currently used methods. GOAL:We describe the development of a multiplex serological protein microarray using recombinant NS1 proteins for detection of medically important viruses within the genus Flavivirus. Sera from clinical flavivirus patients were used for primary development of the protein microarray. RESULTS:Results show a high IgG and IgM sensitivity and specificity for individual NS1 antigens, and limited cross reactivity, even within serocomplexes. In addition, the serology based on this array allows for discrimination between infection and vaccination response for JEV vaccine, and no cross-reactivity with TBEV and YFV vaccine induced antibodies when testing for antibodies to other flaviviruses. CONCLUSION:Based on these data, multiplex NS1-based protein microarray is a promising tool for surveillance and diagnosis of flaviviruses.